Negative electrode for lithium secondary battery and lithium secondary battery including the same

By introducing lithium metal into a three-dimensional carbon structure and coating a fluorine-based polymer, a lithium fluoride protective layer is formed, the problem of lithium branch growth is solved and the life and safety of lithium secondary batteries are improved.

JP7654771B2Active Publication Date: 2025-04-01LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023504612
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-03
Filing Date
2022-04-13
Publication Date
2025-04-01
Estimated Expiration
2042-04-13

Smart Images

  • Figure 0007654771000002
    Figure 0007654771000002
  • Figure 0007654771000003
    Figure 0007654771000003
  • Figure 0007654771000004
    Figure 0007654771000004
Patent Text Reader

Abstract

The present invention relates to an anode for a lithium secondary battery, which includes a three-dimensional carbon structure coated with a fluorine-based polymer; and lithium metal introduced into the outer surface and the interior of the three-dimensional carbon structure coated with a fluorine-based polymer; and the anode can inhibit the formation of lithium dendrites and improve the life characteristics of a lithium secondary battery including the anode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0071885 filed on June 3, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same, and more particularly to a negative electrode for a lithium secondary battery including an outer surface of a three-dimensional carbon structure coated with a fluorine-based polymer and lithium metal introduced into the interior thereof, and a lithium secondary battery including the same. [Background technology]

[0003] Recently, electronic products, electronic devices, communication devices, etc. have been rapidly becoming smaller and lighter, and the need for electric vehicles has become greater in relation to environmental issues. As a result, there is an increasing demand for improved performance of secondary batteries used as power sources for these products.

[0004] In particular, lithium-sulfur (Li-S) batteries are secondary batteries that use a sulfur-based material with an S-S bond (sulfur-sulfur bond) as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material for the positive electrode active material, is an extremely abundant resource, is non-toxic, and has the advantages of having a low weight per unit atom. In addition, the theoretical discharge capacity of lithium-sulfur batteries is 1675mAh / g-sulfur, and the theoretical energy density is 2,600Wh / kg, which is higher than the theoretical energy density of other battery systems currently being researched (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO 2 This is extremely high compared to conventional lithium-ion batteries (1,000Wh / kg; Na-S battery: 800Wh / kg), making it the most promising battery among those developed to date.

[0005] In the discharge reaction of a lithium-sulfur battery, the oxidation reaction of lithium occurs at the negative electrode, and the reduction reaction of sulfur occurs at the positive electrode. Before discharge, sulfur is in the form of a ring-shaped S 8 In this reaction, sulfur stores and generates electrical energy by using an oxidation-reduction reaction in which the S-S bond is broken during a reduction reaction (discharging), decreasing the oxidation number of S, and the S-S bond is re-formed during an oxidation reaction (charging), increasing the oxidation number of S. 8 The linear structure of lithium polysulfide (Li 2 S x , x=8, 6, 4, 2), and finally, when such lithium polysulfides are completely reduced, they finally become lithium sulfide (Li 2 Due to the process of reduction to each lithium polysulfide, the discharge behavior of lithium-sulfur batteries is characterized by a stepwise discharge voltage, unlike lithium-ion batteries.

[0006] However, when lithium metal is used as the negative electrode, its high reactivity during battery operation can cause uneven electron density on the surface of the lithium metal. In this case, lithium dendrites in the form of tree branches are generated on the surface of the electrode, and protrusions form or grow on the surface of the electrode, making the surface very rough. Such lithium dendrites not only reduce the performance of the battery, but in severe cases can damage the separator and cause a short circuit in the battery. As a result, the temperature inside the battery rises, raising the risk of battery explosion and fire, and limiting the lifespan of the battery.

[0007] To solve this problem, research has been conducted on introducing a polymer protective layer or an inorganic solid protective layer to the lithium metal layer, increasing the salt concentration of the electrolyte, and applying appropriate additives, but the effectiveness of these researches in suppressing lithium dendrites is still minimal. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2017-0117649 "Protective film for lithium electrode, lithium electrode and lithium secondary battery including the same" [Patent Document 2] Korean Patent Publication No. 10-2016-0052351 "Lithium metal electrode with stable protective layer and lithium secondary battery including same" Summary of the Invention [Problem to be solved by the invention]

[0009] As a result of extensive research to solve the above problems, the present inventors have found that when lithium metal constituting the anode of a lithium secondary battery is introduced into the outer surface and the interior of a three-dimensional carbon structure coated with a fluoropolymer, the fluoropolymer and the lithium metal react to form lithium fluoride at the interface between the three-dimensional carbon structure coated with a fluoropolymer and the lithium metal, and the lithium fluoride protects the lithium metal and inhibits the formation of lithium dendrites, thereby improving the life of the lithium secondary battery, thereby completing the present invention.

[0010] Therefore, an object of the present invention is to provide a negative electrode for a lithium secondary battery capable of suppressing the formation of lithium dendrites and improving the life of the lithium secondary battery, and a lithium secondary battery including the same. [Means for solving the problem]

[0011] In order to achieve the above objective, The present invention relates to a three-dimensional carbon structure coated with a fluoropolymer; and The three-dimensional carbon structure is coated with a fluorine-based polymer, and lithium metal is introduced into the three-dimensional carbon structure.

[0012] The present invention also provides a lithium secondary battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, The present invention provides a lithium secondary battery, wherein the negative electrode is the negative electrode of the present invention. Effect of the Invention

[0013] In the negative electrode for a lithium secondary battery of the present invention, lithium fluoride having excellent ionic conductivity is formed at the interface between the three-dimensional carbon-based structure coated with a fluorine-based polymer and the lithium metal, thereby protecting the lithium metal and suppressing the growth of lithium dendrites.

[0014] Therefore, a lithium secondary battery including the negative electrode for a lithium secondary battery of the present invention can have improved life characteristics. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic diagram showing a method for producing a negative electrode for a lithium secondary battery according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a negative electrode for a lithium secondary battery in Comparative Example 1. [Diagram 3] 4 is a schematic diagram showing a method for producing a negative electrode for a lithium secondary battery in Comparative Example 2. FIG. [Figure 4] 1 is a SEM photograph of the surface of a three-dimensional carbon structure coated with PTFE produced in Example 1. [Diagram 5] 1 is a SEM photograph of the surface of a three-dimensional carbon structure coated with PTFE produced in Example 2. [Figure 6] 1 is a SEM photograph of the surface of a three-dimensional carbon structure of Comparative Example 2. [Figure 7] 1 is a photograph of negative electrodes for lithium secondary batteries according to Example 1, Example 2, and Comparative Example 2. [Figure 8] 1 is an XPS graph of Experimental Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will now be described in more detail.

[0017] In lithium secondary batteries, preferably lithium-sulfur batteries, that use lithium metal as the anode, lithium dendrites grow on the surface of the anode due to the high reactivity of lithium during operation. This causes the anode to become porous, which reduces the life characteristics of the lithium secondary battery. In addition, unlike other anode active materials such as graphite, lithium anodes do not have a host material that can store lithium, which causes a large volume change in the anode during the charge / discharge process of the lithium secondary battery, which causes a problem of non-uniform lithium usage.

[0018] In order to solve the above problems, it has been attempted to improve the plasticity of lithium and the life characteristics of lithium secondary batteries by introducing a three-dimensional carbon structure capable of supporting lithium metal into a lithium anode. However, since carbon does not have a good affinity with lithium, it is difficult to introduce lithium uniformly into the pores of the three-dimensional carbon structure, making it difficult to solve the above problems.

[0019] Therefore, the present invention aims to provide an anode for a lithium secondary battery that can suppress the growth of lithium dendrites by using a three-dimensional carbon structure coated with a fluorine-based polymer to uniformly introduce lithium metal into the outer surface and inside of the three-dimensional carbon structure, thereby improving the life characteristics of the lithium secondary battery.

[0020] That is, the present invention relates to a three-dimensional carbon structure coated with a fluoropolymer; and The present invention also relates to a negative electrode for a lithium secondary battery, comprising: an outer surface of the three-dimensional carbon structure coated with the fluorine-based polymer, and lithium metal introduced into the interior of the three-dimensional carbon structure.

[0021] The three-dimensional carbon structure is a porous carbon structure, specifically meaning that cylindrical carbon materials are interconnected in three dimensions.

[0022] In this case, the three-dimensional structure may mean that the intersections where two or more lines intersect are distributed in three dimensions.

[0023] In addition, the three-dimensional structure may mean that each basic unit entangled in two dimensions is entangled again in three dimensions to finally have a three-dimensional structure. The term "entangled" may mean that two or more strands cross each other through physical contact.

[0024] The cylindrical carbon material is not particularly limited in type, but may include at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, graphite nanofibers, and activated carbon fibers.

[0025] The porous carbon structure may include at least one selected from the group consisting of carbon paper, carbon felt, and carbon mat. Since the porous carbon structure must maintain its structure even when lithium metal is introduced into the outer surface and inside of the porous carbon structure, the porous carbon structure is preferably carbon paper.

[0026] Since the three-dimensional carbon structure is a state in which the cylindrical carbon material is entangled in three dimensions, void spaces, i.e., pores, may occur within the carbon structure, and thus lithium metal can be introduced into the outer surface and the interior of the three-dimensional carbon structure.

[0027] In the present invention, the three-dimensional carbon structure not only serves as a support for supporting lithium on the outer surface and inside, but also serves as a current collector.

[0028] In the three-dimensional carbon structure, carbon does not have a high affinity for lithium metal, so there is a problem that lithium is not electrochemically uniformly plated on the surface of the three-dimensional carbon structure during operation of the lithium secondary battery. Therefore, in order to induce uniform plating of lithium inside the three-dimensional carbon structure, the surface of the three-dimensional carbon structure is coated with a fluoropolymer in the present invention. If lithium metal is introduced into the outer surface and inside of the three-dimensional carbon structure coated with a fluoropolymer, the fluoropolymer and lithium metal react with each other when lithium metal is introduced to spontaneously form lithium fluoride (LiF). The lithium fluoride has excellent ionic conductivity and can suppress the growth of lithium dendrites, thereby stabilizing the lithium metal. As a result, the life characteristics of the lithium secondary battery including the negative electrode for lithium secondary battery of the present invention can be improved.

[0029] The fluorine-based polymer is not particularly limited in type, but may include at least one selected from the group consisting of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, perfluoroalkoxyalkane, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-chlorotrifluoroethylene copolymer, and ethylene-chlorotrifluoroethylene copolymer, and preferably includes polytetrafluoroethylene.

[0030] The 3D carbon structure coated with a fluoropolymer can be prepared by coating the fluoropolymer by melting it or by coating it with an aqueous solution containing the fluoropolymer, without any particular limitation on the coating method. In the present invention, the 3D carbon structure can be preferably prepared by coating the fluoropolymer with an aqueous solution containing the fluoropolymer.

[0031] The fluoropolymer may be contained in an amount of 2 wt % or more and less than 20 wt %, preferably 5 to 15 wt %, based on the total weight of the aqueous solution containing the fluoropolymer.

[0032] If the fluoropolymer is contained in an amount of less than 2 wt%, the surface of the three-dimensional carbon structure is not sufficiently coated, which may result in the formation of non-uniform lithium fluoride at the interface between the lithium and the three-dimensional carbon structure. If the fluoropolymer is contained in an amount of 20 wt% or more, an over-reaction between the lithium metal and the fluoropolymer occurs, resulting in a large loss of lithium metal, which may result in the failure to improve the life characteristics of the lithium secondary battery.

[0033] The three-dimensional carbon structure coated with the fluorine-based polymer may contain 5 to 30 parts by weight of fluorine per 100 parts by weight of carbon, preferably 10 to 25 parts by weight, and more preferably 15 to 20 parts by weight of fluorine.

[0034] If the fluorine content is less than 5 parts by weight, the fluorine-based polymer coating is not sufficient on the surface of the three-dimensional carbon structure, which may cause a problem that a sufficient amount of lithium fluoride is not formed on the outer surface and inside of the three-dimensional carbon structure. Also, if the fluorine content is more than 30 parts by weight, an over-reaction between the lithium metal and the fluorine-based polymer occurs when the lithium metal is introduced, which may cause a large loss of lithium metal, making it difficult to improve the life characteristics of the lithium secondary battery. At the same time, the negative electrode may easily brittle due to the excessive production of lithium fluoride, which may have a negative effect on the manufacturing process.

[0035] The coating may be performed by a conventional method known in the art, such as doctor blade coating, dip coating, gravure coating, slit die coating, spin coating, comma coating, bar coating, reverse roll coating, screen coating, cap coating, etc., and in the present invention, it is preferable to perform the coating by the dip coating method.

[0036] In the negative electrode for the lithium secondary battery, lithium can be introduced into the outer surface and the interior of the three-dimensional carbon structure coated with a fluoropolymer by laminating lithium foil to the three-dimensional carbon structure coated with a fluoropolymer.

[0037] The interleaving method is not particularly limited as long as it is one that is widely used in the industry, but in the present invention, the lithium foil can be preferably interleaved by a roll press method.

[0038] More specifically, lithium foil is laminated on both sides of a three-dimensional carbon structure coated with a fluoropolymer, and then the laminate is rolled using a roll press to introduce lithium into the outer surface and the interior of the three-dimensional carbon structure coated with a fluoropolymer.

[0039] When lithium metal is introduced into the outer surface and the interior of the three-dimensional carbon structure coated with a fluoropolymer, the lithium metal and the fluoropolymer may spontaneously react to form lithium fluoride. That is, the negative electrode for a lithium secondary battery of the present invention includes lithium fluoride formed by the reaction of the fluoropolymer and lithium metal, and the lithium fluoride may be formed at the interface between the three-dimensional carbon structure coated with a fluoropolymer and lithium.

[0040] The lithium fluoride has excellent ionic conductivity and can suppress the growth of lithium dendrites, and can contribute to stabilizing the lithium metal by acting as a protective layer to protect the surface of the lithium metal. Therefore, the life characteristics of a lithium secondary battery, preferably a lithium-sulfur battery, including the negative electrode for a lithium secondary battery of the present invention can be improved.

[0041] The negative electrode for a lithium secondary battery of the present invention may be a negative electrode for a lithium-sulfur battery.

[0042] The present invention also relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the negative electrode for the lithium secondary battery of the present invention described above.

[0043] The lithium secondary battery according to the present invention may preferably be a lithium-sulfur battery.

[0044] Since the lithium-sulfur battery uses the above-described negative electrode of the present invention as the negative electrode, the formation of lithium dendrite is suppressed, thereby providing a lithium-sulfur battery having excellent life characteristics.

[0045] The positive electrode, separator and electrolyte of the lithium secondary battery are not particularly limited in the present invention and may be any of those known in the art.

[0046] In the present invention, the other positive electrode comprises a positive electrode active material formed on a positive electrode current collector.

[0047] The positive electrode current collector is not particularly limited as long as it supports the positive electrode active material, does not cause a chemical change in the battery, and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, silver, etc., aluminum-cadmium alloy, etc. may be used.

[0048] The positive electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.

[0049] The positive electrode active material is sulfur element (S 8 ) and sulfur compounds. Preferably, inorganic sulfur, Li 2 S n (n≧1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C 2 S x ) n , x=2.5 to 50, n≧2), and most preferably the positive electrode active material may contain inorganic sulfur.

[0050] Therefore, the lithium secondary battery of the present invention may be a lithium-sulfur battery.

[0051] In the case of sulfur contained in the positive electrode active material, since sulfur alone does not have electrical conductivity, it is used in combination with a conductive material such as a carbon material. Thus, the sulfur is contained in the form of a sulfur-carbon composite, and preferably, the positive electrode active material may be a sulfur-carbon composite.

[0052] The sulfur-carbon composite includes a porous carbon material that not only provides a framework to which the sulfur can be uniformly and stably fixed, but also complements the low electrical conductivity of sulfur to facilitate an electrochemical reaction.

[0053] The porous carbon material can be generally prepared by carbonizing various carbon precursors. The porous carbon material contains non-uniform pores, the average diameter of the pores is in the range of 1 to 200 nm, and the porosity or void ratio is in the range of 10 to 90% of the total volume of the porous carbon material. If the average diameter of the pores is less than the range, the size of the pores is merely at the molecular level and impregnation with sulfur is impossible, and conversely, if it exceeds the range, the mechanical strength of the porous carbon material is weakened, making it unsuitable for application to the manufacturing process of an electrode.

[0054] The shape of the porous carbon material may be any shape commonly used in lithium-sulfur batteries, such as spherical, rod-shaped, needle-shaped, plate-shaped, tubular or bulk-shaped, without any limitations.

[0055] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto. Preferably, the porous carbon material may be carbon nanotubes.

[0056] In the sulfur-carbon composite, the sulfur is located at least in one of the inner and outer surfaces of the porous carbon material, and may be present in an area of ​​less than 100%, preferably 1 to 95%, and more preferably 40 to 96% of the entire inner and outer surfaces of the porous carbon material. When the sulfur is present in the inner and outer surfaces of the porous carbon material within the above range, the maximum effect can be exhibited in terms of the electron transfer area and wettability with the electrolyte. Specifically, the sulfur is thinly and uniformly impregnated in the inner and outer surfaces of the porous carbon material within the above range, so that the electron transfer contact area can be increased during charging and discharging. If the sulfur is located in the area of ​​100% of the entire inner and outer surfaces of the porous carbon material, the porous carbon material is completely covered with sulfur, which reduces the wettability with respect to the electrolyte and reduces the contactability, making it unable to transfer electrons and unable to participate in the electrochemical reaction.

[0057] The sulfur-carbon composite may contain 65 to 90 wt %, preferably 70 to 85 wt %, and more preferably 72 to 80 wt %, of the sulfur, based on 100 wt % of the sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite increases relatively, thereby increasing the specific surface area and increasing the content of the binder during the preparation of the positive electrode. This increase in the amount of binder used may ultimately increase the surface resistance of the positive electrode and act as an insulator that prevents electron pass, thereby reducing the battery performance. On the other hand, if the sulfur content exceeds the above range, the sulfur that could not be bonded to the porous carbon material may gather together or be re-sprouted on the surface of the porous carbon material, making it difficult for it to receive electrons and therefore unable to participate in the electrochemical reaction, resulting in a loss of battery capacity.

[0058] The method for producing the sulfur-carbon composite of the present invention is not particularly limited, and may be a method commonly used in the art. For example, the sulfur and the porous carbon material may be simply mixed and then heat-treated to form a composite.

[0059] In addition to the above-mentioned components, the positive electrode active material may further include at least one selected from the group consisting of a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0060] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, the IIIA group elements may include Al, Ga, In, or Tl, and the IVA group elements may include Ge, Sn, or Pb.

[0061] In the positive electrode of the lithium secondary battery of the present invention, the positive electrode active material may be included in an amount of 50 to 95 wt % based on 100 wt % of the entire positive electrode active material layer constituting the positive electrode of the lithium secondary battery. The content of the positive electrode active material is, based on 100 wt % of the entire positive electrode active material layer, a lower limit of 70 wt % or more or 85 wt % or more and an upper limit of 99 wt % or less or 90 wt % or less. The content of the positive electrode active material may be set by combining the lower limit and the upper limit. If the content of the positive electrode active material is less than the above range, the electrochemical reaction of the electrode is difficult to be fully exhibited, and conversely, if it exceeds the above range, the content of the binder is relatively insufficient, resulting in a problem of deterioration of the physical properties of the electrode.

[0062] In addition, the positive electrode active material layer may further include a binder and a conductive material in addition to the positive electrode active material.

[0063] The binder is further used to better adhere the positive electrode active material to the positive electrode current collector.

[0064] The binder supports the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to enhance the binding strength therebetween, and any binder known in the art may be used.

[0065] For example, the binder may be polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyacrylic acid metal salt (Metal-PAA), polymethacrylic acid (PMA), polymethyl methacrylate (PMMA), polyacrylamide (PAM), polymethacrylamide, polyacrylonitrile (PAN), polymethacrylonitrile, polyimide (PI), chitosan, starch, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, hydroxypropyl cellulose, regenerated cellulose, and various copolymers thereof, but is not limited thereto.

[0066] The content of the binder may be 1 to 10 wt % based on 100 wt % of the entire positive electrode active material layer constituting the positive electrode for a lithium secondary battery. If the content of the binder is less than the above range, the physical properties of the positive electrode may be deteriorated and the positive electrode active material may fall off, and if the content exceeds the above range, the proportion of the positive electrode active material in the positive electrode may be relatively reduced and the battery capacity may be reduced, so it is preferable to determine the appropriate content within the above range.

[0067] The conductive material may be further used to further improve the conductivity of the positive electrode active material.

[0068] The conductive material electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material. Any conductive material may be used without limitation.

[0069] For example, the conductive material may be graphite such as natural graphite or artificial graphite; carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, or thermal black; carbon derivatives such as carbon nanotubes or fullerene; conductive fibers such as carbon fibers or metal fibers; carbon fluoride; metal powders such as aluminum or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.

[0070] The conductive material may be included in an amount of 1 to 10 wt%, preferably 4 to 7 wt%, based on 100 wt% of the total positive electrode active material layer constituting the positive electrode. If the content of the conductive material is less than the above range, electron transfer between the positive electrode active material and the current collector is not easy, resulting in a decrease in voltage and capacity. On the other hand, if the content exceeds the above range, the proportion of the positive electrode active material decreases relatively, resulting in a decrease in the total energy (charge) of the battery, so it is preferable to determine the appropriate content within the above range.

[0071] In the present invention, the method for manufacturing the positive electrode is not particularly limited, and a method known to those skilled in the art or various methods modified therefrom may be used.

[0072] For example, the positive electrode may be manufactured by preparing a positive electrode slurry composition containing the above-mentioned components and then coating the composition on at least one surface of the positive electrode current collector.

[0073] The positive electrode slurry composition includes the positive electrode active material described above, and may further include a binder, a conductive material, and a solvent.

[0074] The solvent is one that can uniformly disperse the positive electrode active material, the conductive material, and the binder. As the solvent, water is most preferred as an aqueous solvent, and the water may be distilled water or deionized water. However, the solvent is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water may be used. The lower alcohol may be methanol, ethanol, propanol, isopropanol, butanol, etc., and preferably, these may be mixed with water before use.

[0075] The content of the solvent may be at a level that allows easy coating, and the specific content varies depending on the coating method and device.

[0076] The positive electrode slurry composition may further include, as necessary, a substance commonly used in the relevant technical field for the purpose of improving its function, etc., such as a viscosity modifier, a fluidizing agent, a filler, etc.

[0077] The method of applying the positive electrode slurry composition is not particularly limited in the present invention, and may include, for example, methods such as doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be applied onto the positive electrode current collector by a pressing or lamination method after forming the positive electrode slurry on a substrate separately.

[0078] After the coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time level that allows the solvent to be sufficiently removed, and the conditions may vary depending on the type of solvent, so are not particularly limited in the present invention. Examples include drying with warm air, hot air, or low humidity air, vacuum drying, and drying by irradiation with (far) infrared rays and electron beams. The drying speed is usually adjusted so that the solvent can be removed as quickly as possible within a speed range that does not cause cracks in the positive electrode active material layer due to stress concentration or the positive electrode active material layer to peel off from the positive electrode current collector.

[0079] Furthermore, after the drying, the current collector can be pressed to increase the density of the positive electrode active material in the positive electrode. Examples of the pressing method include die pressing and roll pressing.

[0080] The separator may be located between the positive electrode and the negative electrode.

[0081] The separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transported between the positive electrode and the negative electrode. The separator may be made of a porous non-conductive or insulating material, and may be any material that is generally used as a separator in a lithium secondary battery without any particular limitations. The separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.

[0082] The separation membrane is preferably one that has low resistance to ion migration in the electrolyte and has excellent moisture-absorbing capacity for the electrolyte.

[0083] The separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, or the like, or a polyolefin-based porous membrane may be used, but is not limited thereto.

[0084] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate that is generally used in electrochemical devices can be used. For example, the porous substrate may be a polyolefin such as polyethylene or polypropylene, a polyester such as polyethyleneterephthalate or polybutyleneterephthalate, a polyamide, a polyacetal, a polycarbonate, a polyimide, a polyetheretherketone, a polyethersulfone, a polyphenyleneoxide, a polyphenylenesulfide, a polyethylenenaphthalate, a polytetrafluoroethylene, a polyvinylidenefluoride, a polyvinyl chloride, a polyacrylonitrile, a cellulose, a nylon, or a poly(p-phenylene benzobisoxazole). The material may include one or more materials selected from the group consisting of benzobisoxazole and polyarylate.

[0085] The thickness of the porous substrate is not particularly limited, but is 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but if the thickness is smaller than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.

[0086] The average diameter and porosity of the pores in the porous substrate are not particularly limited, but are in the range of 0.001 to 50 μm and 10 to 95%, respectively.

[0087] The electrolyte is a non-aqueous electrolyte containing a lithium salt, which is composed of a lithium salt and an electrolytic solution. As the electrolytic solution, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used.

[0088] The lithium salt of the present invention is a substance that is easily dissolved in a non-aqueous organic solvent, and is, for example, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiB(Ph) 4 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , LiSO 3 CH 3 , LiSO 3 CF 3 , LiSCN, LiC(CF 3 SO 2 ) 3 , LiN(CF 3 SO 2 ) 2 , lithium chloroborane, lithium lower aliphatic carboxylate, and lithium tetraphenylborate.

[0089] The concentration of the lithium salt is 0.2 to 2M, specifically 0.6 to 2M, more specifically 0.7 to 1.7M, depending on several factors such as the exact composition of the electrolyte mixture, the solubility of the salt, the conductivity of the dissolved salt, the charging and discharging conditions of the battery, the operating temperature, and other factors known in the lithium battery field. If less than 0.2M is used, the electrolyte conductivity may be reduced, resulting in a decrease in electrolyte performance, and if more than 2M is used, the viscosity of the electrolyte may increase, resulting in the lithium ion (Li+ ) may have reduced mobility.

[0090] The non-aqueous organic solvent must be capable of dissolving lithium salts well. Examples of the non-aqueous organic solvent of the present invention include N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl Aprotic organic solvents such as diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triesters, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc., may be used, and the organic solvent may be one or a mixture of two or more organic solvents.

[0091] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionic dissociation groups.

[0092] The inorganic solid electrolyte of the present invention is, for example, Li 3 N, LiI, Li 5 NI 2 , Li 3 N-LiI-LiOH, LiSiO 4 , LiSiO 4 -LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO4 -LiI-LiOH, Li 3 PO 4 -Li 2 S-SiS 2 Nitrides, halides, sulfates, etc. of Li such as Li can be used.

[0093] The positive electrode, separator, and electrolyte included in the lithium secondary battery may be prepared using conventional ingredients and manufacturing methods, and the shape of the lithium secondary battery is not particularly limited, but may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0094] Hereinafter, preferred examples will be presented to facilitate understanding of the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the accompanying claims.

[0095] <Manufacturing negative electrodes for lithium-sulfur batteries> Example 1 Polytetrafluoroethylene (PTFE, product name: Teflon) TM PTFE DISP 30) was added to distilled water to prepare a fluoropolymer aqueous solution containing 10% by weight of PTFE based on the total weight of the fluoropolymer aqueous solution.

[0096] Carbon paper was coated with the fluoropolymer aqueous solution and then dried to produce a 3D carbon structure coated with PTFE.

[0097] Lithium foil with a thickness of 60 μm was laminated on both sides of the PTFE-coated 3D carbon structure, and then it was rolled with a roll press to introduce lithium into the external surface and the interior of the PTFE-coated 3D carbon structure to manufacture the anode (Figure 1). At this time, a film with no adhesive properties to lithium was used for the purpose of deforming the surface of the lithium foil that comes into contact with the rolling roll.

[0098] Heat is generated during the rolling process, which is believed to be due to an exothermic reaction that occurs when lithium fluoride is produced by the spontaneous reaction of PTFE and lithium.

[0099] Example 2 A negative electrode was manufactured in the same manner as in Example 1, except that a fluoropolymer aqueous solution containing 20 wt % PTFE based on the total weight of the fluoropolymer aqueous solution was used (FIG. 1).

[0100] Heat was generated during rolling, which is believed to be due to an exothermic reaction occurring when lithium fluoride was produced by the spontaneous reaction of PTFE and lithium. In addition, within 1-2 hours after production, the negative electrode for the lithium secondary battery of Example 2 began to turn brown on the surface, with uneven marks forming, and the surface becoming rough. This is believed to be due to an over-reaction of lithium metal with PTFE, and it was confirmed that the electrode became more easily brittle.

[0101] Comparative Example 1 The negative electrode was fabricated by laminating 60 μm-thick lithium foil to both sides of a 10 μm-thick copper current collector (Figure 2).

[0102] Comparative Example 2 Carbon paper was used in the three-dimensional carbon structure.

[0103] Lithium foil with a thickness of 60 μm was laminated on both sides of the carbon paper, and then rolled with a roll press to introduce lithium into the external surface and interior of the 3D carbon structure to manufacture the anode (Figure 3). At this time, a film with no adhesive properties to lithium was used for the purpose of deforming the surface of the lithium foil that comes into contact with the rolling roll.

[0104] Experimental example 1. Measurement of fluorine and carbon content ratio of 3D carbon support coated with fluoropolymer The fluorine content coated on the three-dimensional carbon structure of the negative electrode for the lithium-sulfur battery of Example 1 and Example 2 was measured.

[0105] The fluorine content was measured using SEM point EDS.

[0106] It was confirmed that in the PTFE-coated three-dimensional carbon structure of Example 1, fluorine (F) was contained in an amount of 19 parts by weight per 100 parts by weight of carbon (C) (F / C ratio=0.19).

[0107] In addition, it was confirmed that in the PTFE-coated three-dimensional carbon structure of Example 2, fluorine (F) was contained in an amount of 33 parts by weight per 100 parts by weight of carbon (C) (F / C ratio=0.33).

[0108] Experimental Example 2. Measurement of weight per unit area of ​​PTFE-coated 3D carbon structure and copper current collector The weights per unit area of ​​the PTFE-coated three-dimensional carbon structure prepared in Example 1 and the copper current collector of Comparative Example 1 were measured.

[0109] The weight per unit area of ​​the PTFE-coated three-dimensional carbon structure produced in Example 1 was 3.3 mg / cm 2 The weight per unit area of ​​the copper current collector in Comparative Example 1 was 9 mg / cm 2 It was.

[0110] The negative electrode for the lithium-sulfur battery of Example 1 is an anode in which lithium metal is introduced on the outer surface and inside of a three-dimensional carbon structure coated with PTFE, which is a fluoropolymer, and the negative electrode for the lithium-sulfur battery of Comparative Example 1 is an anode in which lithium foil is laminated on both sides of a copper current collector.

[0111] It was confirmed that the PTFE-coated three-dimensional carbon structure of Example 1 had a lower weight per unit area than the copper current collector of Comparative Example 1.

[0112] This shows that the anode of the present invention has a small loss in energy density per unit weight, and thus can reduce the decrease in energy density.

[0113] Experimental Example 3. Surface analysis of negative electrodes for lithium-sulfur batteries The surface of the negative electrode for the lithium-sulfur battery prepared in Example 1 and Example 2 was analyzed by XPS to confirm whether lithium fluoride was formed.

[0114] As a result, it was confirmed that Example 1 contained fluorine (F) at 1.5% (atomic percent), and Example 2 contained 2.4% (atomic percent) (FIG. 8).

[0115] From this, it was found that in the anode of the present invention, the fluoropolymer reacts with lithium to form lithium fluoride (LiF), and the greater the amount of coated fluoropolymer, the greater the amount of lithium fluoride formed.

[0116] Experimental Example 4: Measurement of life characteristics of lithium-sulfur batteries The positive electrode active material, sulfur-carbon (CNT) composite (S:C = 75:25 (weight ratio)), conductive material (VGCF) and binder (Li-PAA) were mixed in a weight ratio of 87.5:5:7.5 and added to distilled water to prepare a positive electrode slurry.

[0117] The positive electrode slurry was applied to both sides of an aluminum current collector, dried at a temperature of 80° C., and rolled using a roll press to prepare a positive electrode. At this time, the loading amount was 3.5 mAh / cm 2 It was.

[0118] 1M LiTFSI and 1% by weight LiNO 3 The electrolyte was prepared by dissolving the compound in an organic solvent consisting of 1,3-dioxolane (DOL) and dimethyl ether (DME) in a 1:1 volume ratio.

[0119] A polyethylene porous film with a thickness of 16 μm and a porosity of 68% was used as the separator.

[0120] As the negative electrodes, the negative electrodes prepared in Example 1, Example 2, Comparative Example 1, and Comparative Example 2 were used, respectively.

[0121] A separator was inserted between the positive and negative electrodes and stacked to assemble a pouch cell, and then an electrolyte was injected and sealed to prepare each lithium-sulfur battery.

[0122] Each of the lithium-sulfur batteries was operated in CC mode at 25° C. with a 0.2 C charge and 0.3 C discharge cycle (2.5 / 1.8 upper / lower limits, respectively) to measure the cycle life at which 80% of the initial capacity was maintained. The results are shown in Table 1 below.

[0123] [Table 1]

[0124] The results in Table 1 show that the life characteristics of the lithium-sulfur battery including the anode of Example 1, which is the anode of the present invention, are the best. The anode of Example 1 has lithium metal introduced into the outer surface and the interior of a three-dimensional carbon structure coated with a fluoropolymer. Specifically, the three-dimensional carbon structure coated with a fluoropolymer of Example 1 was prepared using a fluoropolymer aqueous solution containing 10 wt% of fluoropolymer based on the total weight of the fluoropolymer aqueous solution, and the three-dimensional carbon structure coated with a fluoropolymer of Example 1 contained 19 wt parts of fluorine based on 100 wt parts of carbon.

[0125] In other words, the fluoropolymer spontaneously reacts with lithium metal to form lithium fluoride at the interface between the fluoropolymer-coated three-dimensional carbon structure and lithium metal. The lithium fluoride protects the lithium metal and inhibits the growth of lithium dendrites due to its high ionic conductivity, thereby improving the life characteristics of lithium-sulfur batteries.

[0126] The negative electrode of Comparative Example 1 was a current collector with lithium metal laminated thereon, and Comparative Example 2 was a three-dimensional carbon structure with lithium metal introduced on its outer surface and inside. The lithium-sulfur batteries including these were unable to inhibit the growth of lithium dendrites, and showed poor life characteristics.

[0127] The negative electrode of Example 2 is a structure in which lithium metal is introduced into the outer surface and the inside of a three-dimensional carbon structure coated with a fluoropolymer. Specifically, the three-dimensional carbon structure coated with a fluoropolymer of Example 2 is manufactured using a fluoropolymer aqueous solution containing 20 wt% of fluoropolymer based on the total weight of the fluoropolymer aqueous solution, and the three-dimensional carbon structure coated with a fluoropolymer of Example 2 contains 33 wt% of fluorine based on 100 wt% of carbon. If the fluoropolymer is contained in an amount of 20 wt% or more based on the total weight of the fluoropolymer aqueous solution, an over-reaction occurs between the lithium metal and the fluoropolymer, resulting in a large loss of lithium metal. As a result, the life characteristics of the lithium-sulfur battery including the negative electrode of Example 2 were not improved.

[0128] As a result, it was confirmed that if a 3D carbon structure coated with a fluoropolymer is manufactured using a fluoropolymer aqueous solution containing 20 wt% or more of a fluoropolymer based on the total weight of the fluoropolymer aqueous solution, the fluorine content exceeds 30 parts by weight per 100 parts by weight of carbon in the 3D carbon structure coated with the fluoropolymer, and therefore, the reaction between the fluoropolymer and lithium metal occurs excessively, increasing the loss of lithium metal, and thus making it impossible to improve the life characteristics of the lithium-sulfur battery.

Claims

1. A three-dimensional carbon structure coated with a fluoropolymer; and lithium metal is introduced into the outer surface and the interior of the three-dimensional carbon structure coated with the fluoropolymer; The fluorine-based polymer includes at least one selected from the group consisting of polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, perfluoroalkoxyalkane, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-chlorotrifluoroethylene copolymer, and ethylene-chlorotrifluoroethylene copolymer.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the three-dimensional carbon structure is a porous carbon structure.

3. 3. The negative electrode for a lithium secondary battery according to claim 2, wherein the porous carbon structure comprises at least one material selected from the group consisting of carbon paper, carbon felt, and carbon mat.

4. 2. The negative electrode of claim 1, wherein the three-dimensional carbon structure coated with the fluorine-based polymer contains 5 to 30 parts by weight of fluorine per 100 parts by weight of carbon.

5. The negative electrode for a lithium secondary battery as described in claim 1, characterized in that it contains lithium fluoride.

6. 6. The negative electrode for a lithium secondary battery according to claim 5, wherein the lithium fluoride is formed at the interface between the three-dimensional carbon structure coated with a fluorine-based polymer and lithium metal.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the fluorine-based polymer comprises polytetrafluoroethylene.

8. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode for a lithium secondary battery is a negative electrode for a lithium-sulfur battery.

9. A lithium secondary battery comprising: a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte, The negative electrode of claim 1 , wherein the negative electrode is a lithium secondary battery.

10. 10. The lithium secondary battery according to claim 9, wherein the lithium secondary battery is a lithium-sulfur battery.

Citation Information

Patent Citations

  • Lithium battery negative electrodes

    JP2015520926A

  • Lithium electrodes and lithium secondary batteries containing them

    JP2017517853A

  • Passivation layer for lithium electrode, electrode and lithium secondary battery comprising the same

    KR1020170117649A

  • KR10‐2016‐0052351

  • KR10‐2017‐0117649